Design and Validation of an Assessment Tool for Educational Mobile Applications Used with Autistic Learners - Mònica Sanromà-Giménez; José Luis Lázaro Cantabrana; Mireia Usart Rodríguez; Mercè Gisbert-Cervera (Springer, 2021)
This work presents the design and validation process for a tool to evaluate educational mobile applications for autistic learners. The project was developed in several stages. First, we reviewed and analysed the literature. Second, we conducted a Delphi study with experts (n=12) from different backgrounds (educational technology, accessibility, app developers and autism specialist teachers) selected using the calculated expert competence coefficient. And finally, we conducted a pilot test with trainee (n=51) and in-service (n=9) teachers who evaluated a selection of 11 apps. The data collected was used to study the factor structure of the tool, its reliability and usability. In this paper we present the resulting questionnaire consisting of 36 items grouped into six sections: "Information about the evaluator", "Technical and descriptive characteristics", "Pedagogical characteristics in relation to autism", "General pedagogical characteristics", "Characteristics for educational inclusion and accessibility", and "Professional satisfaction". The results condense the questionnaire to two factors and indicate that the tool is valid, reliable and useful for assessing the properties of apps and for facilitating the learning process of people with autism.